Enhancing analytical performance of tyrosinase-based sensors with nanoparticles for detection of isoproterenol - Oktay, Aysel; Kurbanoglu, Sevinc; Gundogdu, Gulsum; Ustundag, Cem Bulent; Scheller, Frieder W.; Yarman, Aysu (Tubitak Scientific & Technological Research Council Turkey, 2025)
In this work, electrochemical biosensors utilizing tyrosinase (Tyr) for the detection of the nonselective beta-adrenergic agonist isoproterenol (ISO) are presented. Three different configurations for immobilizing Tyr on a graphite electrode (GE) are compared: (1) GE modified with poly(diallyldimethylammonium chloride) (PDADMAC), PDADMAC/Tyr/GE; (2) PDADMAC combined with iridium nanoparticles (IrNPs) in a stepwise preparation, resulting in PDADMAC/IrNPs/Tyr/GE; and (3) a composite of PDADMAC and IrNPs mixed with Tyr at a 1:1 (v:v), forming PDADMAC/(IrNPs-Tyr)/GE. Surface morphology was characterized using scanning electron microscopy (SEM). Cyclic voltammetry (CV) and amperometry were applied to characterize the biosensor's performance. Within the linear range of 5 mu M to 211 mu M, the biosensor PDADMAC/Tyr/GE exhibited a limit of detection (LOD) of 1.4 mu M and a limit of quantification (LOQ) of 4.1 mu M. PDADMAC/IrNPs/Tyr/GE displayed improved sensitivity with an LOD of 0.9 mu M and an LOQ of 2.8 mu M. The configuration PDADMAC/(IrNPs-Tyr)/GE demonstrated the best performance with an LOD of 0.3 mu M and an LOQ of 0.8 mu M. The slopes (0.0147 mu A/M, 0.0096 mu A/M, and 0.0031 mu A/M for PDADMAC/(IrNPs-Tyr)/GE, PDADMAC/IrNPs/Tyr/ GE, and PDADMAC/Tyr/GE, respectively) of the concentration dependencies for the three sensor modifications (which represent the analytical sensitivity) demonstrate the achieved enhancement of analytical performance by IrNPs. Furthermore, the biosensor's ability to detect ISO in the presence of potential interferences, such as ascorbic acid, uric acid, and paracetamol, was assessed. Additionally, we demonstrated the biosensor's potential to detect ISO in diluted spiked human serum samples.
Keywords: Isoproterenol (isoprenaline); electrochemical biosensor; tyrosinase; iridium nanoparticles; poly(diallyldimethylammonium chloride); AMPEROMETRIC GLUCOSE BIOSENSOR; CARBON NANOTUBES; REDUCED GRAPHENE; IONIC LIQUID; ENZYME; ACID; OXIDE; NOREPINEPHRINE; ACETAMINOPHEN; Chemistry; Engineering